Factors influencing e-marketplace adoption in agricultural micro-enterprises. (22nd September 2010) - Brush, Gregory J.; McIntosh, Duncan
Electronic marketplaces (e-marketplaces) present a business-tobusiness (B2B) trading environment where firms can benefit from increased choice among trading partners, and other efficiencies gained through electronic exchange. B2B e-marketplaces have only recently emerged in New Zealand; however, there is already doubt whether predicted benefits are being realised. The study draws on Tornatzky and Fleischer's (1990) adoption model to explore motivations and barriers to e-marketplace adoption that agricultural micro-enterprises experience. Key barriers include conflict with pre-existing relationships, risk perceptions, ease of use and infrastructure problems. Dominant motivations include the ability to exclude agent middlemen, a reduction in transaction costs, and market reach.